The Legal Protection of Commercial Marks Based on the First to File Principle in Act No. 20 of 2016 - Adrian Winata; Budi Santoso (Universitas Islam Sultan Agung, 2023)
In this day and age, business competition is very tight, therefore, to support increased sales in a business field, a brand is needed. Brands are very influential on the sale of a product, the more well-known a brand is, the easier the brand can be absorbed by the public. Many companies engaged in the cosmetics sector are competing to raise their trademark names so that they are better known among the public, but the more intense business competition in the cosmetic sector, the more legal issues and individuals who want to find opportunities to imitate other trademarks that already well-known so that their products are quickly remembered and known by the public. This case often occurs in the field of Intellectual Property Rights or IPR, especially in the field of Brands, as in the case of MS Glow and PS Glow. The mark itself has been protected in Act No. 20 of 2016 concerning marks and geographical indications. The first to file principle is applied in this trademark law to prevent parties from wanting to take advantage of the existing big brands. How the Trademark Law protects the MS Glow Brand from the owner of the legal brand so that it is not copied by others attracts the attention of the author to discuss this matter.